Pendampingan Pra Nikah Sebagai Solusi Mencari Pasangan Ideal Bagi Santri Senior Pondok Pesantren Miftahul Mubtadiin Putra Ar-Ridlo Krempyang Tanjunganom Nganjuk - Abdul Basit Misbachul Fitri; Khusnul Kholik (Janaka, Jurnal Pengabdian Masyarakat, 2020)
Pre-marital training as a solution to finding the ideal partner in the covid-19 pandemic season for administrators and students is a breakthrough made by the community service team of STAI Darussalam Nganjuk to increase the potential of students in understanding the importance of a marriage contract legally according to religion and the government. This activity has never been held in a boarding school before, in collaboration with the education section of the boarding school for the Miftahul Mubtadiin Putra Ar-Ridlo boarding school, the program was held on Wednesday, October 14 2020 at around 21.00 WIS. located in the al-Manshur building, the community service team and others distributed the pretest to participants to be filled in and then collected to the committee before the activity started, the participants also filled in attendance to find out the number of participants. After completing the pre-test training, the resource person explained about legal marriage according to religion and State. Because a marriage that is carried out outside the supervision of a Marriage Registration Officer has no legal force. By using a single power point, the resource person appointed the participants to practice the marriage contract process.